2004
DOI: 10.1128/aem.70.9.5538-5545.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Highly Enriched Dehalococcoides -Containing Culture That Grows on Vinyl Chloride and Trichloroethene

Abstract: A highly enriched culture that reductively dechlorinates trichloroethene (TCE), cis-1,2-dichloroethene (cDCE), and vinyl chloride (VC) to ethene without methanogenesis is described. The Dehalococcoides strain in this enrichment culture had a yield of (5.6 ؎ 1.4) ؋ 10 8 16S rRNA gene copies/mol of Cl ؊ when grown on VC and hydrogen. Unlike the other VC-degrading cultures described in the literature, strains VS and BAV1, this culture maintained the ability to grow on TCE with a yield of (3.6 ؎ 1.3) ؋ 10 8 16S rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
216
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(225 citation statements)
references
References 17 publications
6
216
3
Order By: Relevance
“…The Dehalococcoides-containing consortium KB-1 used for bioaugmentation contains methanogens and rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120320 CO 2 -reducing acetogens [29]. Both methanogenic Archaea and acetogenic Bacteria are known to synthesize cobamides with different lower ligands (figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The Dehalococcoides-containing consortium KB-1 used for bioaugmentation contains methanogens and rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120320 CO 2 -reducing acetogens [29]. Both methanogenic Archaea and acetogenic Bacteria are known to synthesize cobamides with different lower ligands (figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…are widespread in the environment (Dennis et al, 2003;Duhamel et al, 2004;Fennell et al, 2001;Gu et al, 2004;Kassenga et al, 2004;Löffler et al, 2000;Major et al, 2002;Richardson et al, 2002;Smits et al, 2004) and have been shown to dechlorinate PCDD/Fs (Bunge et al, 2001(Bunge et al, , 2003Yoshida et al, 2005;Hiraishi et al, 2005;Ahn et al, 2007. Our previous study demonstrated the increase of a Dehalococcoides population along with the dechlorination of weathered PCBs in Anacostia River (Washington, DC) sediment microcosms, suggesting their potential role in PCB dechlorination .…”
Section: Discussionmentioning
confidence: 99%
“…2-2 and 2-4), however, could not explain the differences in the PCB dechlorination activity observed in the two different haloprimer treatments. The 16S rRNA genes of Chloroflexi species are highly conserved and do not correspond with different dechlorination substrate specificities Duhamel et al, 2004;He et al, 2005;Kube et al, 2005;Sung et al, 2006). For this reason, Band 1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations